Everywhere “Shoddy Gaud and Fraud”: The Inherent Fraudulence of Black Suffrage in Walt Whitman’s Democratic Vistas - Pettit, Audrey (Meliora, 2026)
Following Black men’s enfranchisement under the 15th Amendment, American poet, essayist, and journalist Walt Whitman authored Democratic Vistas—his 1871 treatise on democracy in post-Civil War America. The text has been canonized as required reading in democratic theory; political philosopher Cornel West deemed it a “landmark text in modern democratic thought” (quoted in Sollenberger 203). Indeed, some scholars argue that American civilization cannot be understood without Walt Whitman: he is “America’s poet,” modernist writer Ezra Pound claimed. “He is America” (Pound 13). Still, few have reckoned with Whitman’s response to Black suffrage. In Democratic Vistas, Whitman asserts that the soul of American democracy lies not in the faulty mechanisms of voting and political representation but in the purity of its cultural identity. The expansion of the franchise corrupted and confused this identity—heretofore based on whiteness and maleness—by eliminating the boundaries that separated enslaved and slaveholder, Black and white, voter and non-voter. Whitman thus interrogates whether these newly enfranchised men can ever become legitimate voters by engaging in a theatrical, written, and visual tradition that casts Black Americans as farcical, immoral, and fundamentally incapable of adopting the spiritual conditions of citizenship. In so doing, he lays the foundation for an aesthetic discourse that ontologically equates Black voters to frauds.